Serum Eotaxin-1 is Increased in Extremely Low Birth Infants with Bronchopulmonary Dysplasia or Death - Kandasamy, Jegen (Pediatr Res, 2015)
BACKGROUND: Early systemic inflammation in extremely low birth weight (ELBW) infants is associated with an increased risk of bronchopulmonary dysplasia (BPD). Our objective was to identify circulating biomarkers and develop prediction models for BPD/death soon after birth. METHODS: Blood samples from postnatal day 1 were analyzed for CRP by ELISA and for 39 cytokines/chemokines by a multiplex assay in 152 ELBW infants. The primary outcome was physiologic BPD or death by 36w. CRP, cytokines, and clinical variables available at ≤24 h were used for forward stepwise regression and Classification and Regression Tree (CART) analysis to identify predictors of BPD/death. RESULTS: Overall, 24% developed BPD and 35% died or developed BPD. Regression analysis identified birth weight and eotaxin (CCL11) as the two most significant variables. CART identified FiO(2) at 24h (11% BPD/death if FiO(2) ≤28%, 49% if >28%) and eotaxin in infants with FiO(2)>28% (29% BPD/death if eotaxin was ≤84 pg/ml; 65% if >84) as variables most associated with outcome. CONCLUSION: Eotaxin measured on the day of birth is useful for identifying ELBW infants at risk of BPD/death. Further investigation is required to determine if eotaxin is involved in lung injury and pathogenesis of BPD.